Legal Implications of Subsidiary Bankruptcy on the Parent Stated-Owned Enterprise - Alika, Nandia Fanis; Shafa Annisa, Nur (Jurnal Cakrawala Hukum, 2025)
Bankruptcy is an act of confiscating all the assets of the Bankrupt Debtor, the management of which is carried out by the Curator under the supervision of the Supervisory Judge, by the provisions of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. A bankruptcy application can be submitted to a Limited Liability Company provided that it meets the requirements stated in Article 2 paragraph (1) of Law Number 37 of 2004. This Limited Liability Company does not only include ordinary Limited Liability Companies but also subsidiaries of State- Owned Enterprises (BUMN). This study employs a normative legal approach, examining the legal system that regulates the legal consequences for BUMN as the parent company if its subsidiary is declared bankrupt. If a BUMN subsidiary goes bankrupt, the BUMN parent company cannot be held accountable, as the two entities are separate entities. However, several conditions allow the BUMN parent company to be held accountable for the bankruptcy of its subsidiary, for example, if the parent company is involved in determining management, finances, or business decisions that lead to the subsidiary experiencing finansial difficulties. Additionally, the parent company of a BUMN can also be subject to bankruptcy if it acts as a corporate guarantor for its subsidiary.